Building Reproductive Genetic Services from Bottom Up: Over 30-year Experience of a Major Prenatal Diagnostic Center in Guangdong Province - Yin, MD, PhD, Aihua; Zhang, MD, PhD, Xiaozhuang; Ye, MD, MBA, Ning; Wu, MD, Jing; Pan, MS, Xiaoying; Guo, MS, Li (North American Journal of Medicine and Science, 2013)
Prenatal diagnosis plays an important role in preventing birth defects and improving birth quality. Through continuous efforts from the past three decades, the Guangdong Women and Children’s Hospital has transform a small department of medical genetics into a prenatal center for genetic disease diagnosis and treatment (PCGDDT). A wide spectrum of genetic tests including clinical cytogentics, biochemical screening and molecular genetics has been performed. A biobank of patient specimens for translational research has been established. PCGDDT has been one of the key disciplines of Guangdong Women and Children Hospital and master degree training hospital for Guangzhou Medical University, state-level professional training base in clinical and laboratory technology, and priority specialty of Guangdong Province. Our experience represents a bottom up approach to build sustainable hospital-based and institute-affiliated genetic services in China. [N A J Med Sci. 2013;6(4):216-218. DOI: 10.7156/najms.2013.0604216]